The Incentive-Compatible Design of Deposit Insurance and Bank Failure Resolution : Concepts and Country Studies - Beck, Thorsten (World Bank, Washington, DC, 2014)
Deposit insurance schemes and bank failure resolution systems are asked to fulfill conflicting public policy objectives: on the one hand, they are supposed to protect small depositors and prevent contagion risks from bank runs; on the other hand, they are supposed to minimize aggressive risk taking by banks. Beck discusses the incentive-compatible design and interaction of both components of the financial safety net and describes and compares three countries with different safety net arrangements-Brazil, Germany, and Russia.